ANALISIS MANAJEMEN LABORATORIUM IPA TERHADAP KOMPETENSI PESERTA DIDIK - Ardiansyah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2019)
Natural Sciences learning laboratory activities are an integral part of teaching and learning activities, This shows how important the role of laboratory activities to achieve the goals of science education. Through laboratory activities, students will be given the opportunity to encourage curiosity and the desire to try, test and reason the theories obtained. The purpose of this study was to analyze the management of a science laboratory in SMP Negeri 4 Sojol. The research method uses qualitative methods and descriptive analysis. The research subjects were the head of the laboratory and the science subject teacher and the students at SMP Negeri 4 Sojol. Data collection techniques through observation, interviews and student learning outcomes. Based on the results of the study, the availability of natural science practicum tools in SMP Negeri 4 Sojol, the average availability of practical tools and materials 68.33% classified as complete categories, the average presentation of the feasibility of practical tools and materials 90.67% included in the excellent category based on the Ministry of Education number 24 of 2007. the effectiveness of practicum implementation in SMP Negeri 4 Sojol is classified as effective category with an average presentation of practicum at 85%. Coupled with an average increase in cognitive competencies average preetest 58 increase in posttest by as much as 87 in addition to the average value of competence in the areas of psychomotor average preetest obtained 60 and posttest 90 showed a significant increase competency knowledge and skills of learners. Success in the cognitive domain will also have a positive impact on the development of the psychomotor domain (skills) of students. Management of laboratory facilities and infrastructure planning in improving the quality of learning in schools must be planned by the head of the laboratory, planning science teachers by preparing learning tools and identifying the subject matter to be practiced in the laboratory, laboratory administration governance supported by good organization from the leadership of policy makers in school. Implementation of laboratory facilities and infrastructure management in improving the quality of learning in schools including procurement, inventory, storage, structuring, use, and maintenance. Supervision carried out by the principal is in accordance with the provisions, to be more efficient the school should make a program or schedule of supervision processes to be more controlled and run well and smoothly.